Bruck Syndrome: A Rare Disorder in New-Born with Fractures and Contractures - Dhaubhadel, Suraj; Baniya, Bimala; Joshi, Hema; Chapagain, Ram Hari; Paudel, Krishna Prasad (Journal of Nepal Paediatric Society, 2018)
Bruck syndrome is a very rare autosomal recessive syndrome consisting of bone fragility and congenital joint contractures. It is considered as a combination of arthrogryposis multiplex congenita and osteogenesis imperfecta, while some consider it as the autosomal recessive variant of osteogenesis imperfecta. According to the genotype, it has been classified into types 1 and 2. To our knowledge, only about 28 patients of this syndrome have been reported so far worldwide with none been reported from Nepal. Here, we present a patient with generalized osteopenia, bilateral femur fracture and congenital joint contractures of distal extremities.